DESAIN PESANTREN MINHAJUSSALAM TINGKAT MTS DI KECAMATAN GUNUNG RAJA KABUPATEN TANAH LAUT - Halimatussa’diah, Gusti; Wastuty, Prima Widya (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2024)
Flood is a natural disaster that can harm the environment, especially human settlements. The potential for flooding can be seen based on environmental characteristics, one of which is a swamp. Gunung Raja, Bati-Bati District, Kab. Tanah Laut is one of the residential areas that stands on swampland. Swampy land has high tide times and can potentially flood when it encounters high rainfall. Knowing the potential for flooding, we need a building that is responsive to tides. Buildings that have the potential for disaster response are educational facilities/schools, namely the Minhajussalam Islamic Boarding School. By creating a design using the Contextual Architecture method, it is hoped that this design can create a building that is responsive to sea tides and can become an emergency facility for the surrounding color in the event of a flood.